Counseling on the Introduction of Safe Syrup on the Knowledge Level of the Community at Kalisoka Village - Wulandari, Prihastini Setyo; Pramiastuti, Oktariani; Istriningsih, Endang; Murti, Fiqih Kartika; Firsty, Girly Risma; Afina, Afina; Alfiraza, Ery Nourika (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Health is the most important aspect in people’ lives. One of the efforts made in maintaining the health is by doing self-medication which is defined as an effort to cure themselves and can cause problems if they have limited knowledge. Delivering infromation on how to store and the time limit for using medicine after the packaging is opened is one of the responsibilities of pharmaceutical personnel which is important to know. One of the most widely used medicine by the public is syrup. Self-medication is widely practiced in the community to treat diseases or symptoms of diseases by buying drugs at pharmacies or drug stores so that they need clear information to make decisions about the type and amount of drugs to be used and how to use them correctly. To increase the community knowledge on choosing and giving safe syrup, it is necessary to conduct counselling on the introduction of safe syrup. The activity was given to the PKK mothers and cadres at Kalisoka village Tegal regency. It used pretest and posttest to take the data. After the activity, the result showed that the participants had anthusiasm and the knowledge increased.